2003
DOI: 10.1128/jcm.41.6.2768-2773.2003
|View full text |Cite
|
Sign up to set email alerts
|

Nocardia veterana Isolated from Ascitic Fluid of a Patient with Human Immunodeficiency Virus Infection

Abstract: Nocardia veterana is a recently characterized species within the genus Nocardia, and only three human clinical isolates have been reported for this species. We describe a case of ascitic fluid infection in an immunocompromised patient due to N. veterana. To our knowledge, this is the first report of a Nocardia sp. strain from ascitic fluid and the fourth report of N. veterana isolated from human samples. Chemotaxonomic methods showed the strain to belong to the genus Nocardia, and identification to the species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…Positive results were for pyrazinamidase, alkaline phosphatase, ␣-glucosidase, and gelatin hydrolysis. These results prompted us to determine the 16S rRNA gene sequence of the isolate as previously described (3). Briefly, the 16S rRNA gene was amplified by PCR with the primers Al (5Ј-AGRGTTYGATYCTGGCTCAGGAYG-3Ј) and rJ (5Ј-GGTTACCTTGTTACGACTT-3Ј) (5).…”
mentioning
confidence: 99%
“…Positive results were for pyrazinamidase, alkaline phosphatase, ␣-glucosidase, and gelatin hydrolysis. These results prompted us to determine the 16S rRNA gene sequence of the isolate as previously described (3). Briefly, the 16S rRNA gene was amplified by PCR with the primers Al (5Ј-AGRGTTYGATYCTGGCTCAGGAYG-3Ј) and rJ (5Ј-GGTTACCTTGTTACGACTT-3Ј) (5).…”
mentioning
confidence: 99%
“…A pulmonary infection was diagnosed for most of those patients, whereas 2 patients showed an abdominal localization (7,15) and another had a mycetoma (9). Here, we present the first description of a brain abscess caused by Nocardia veterana.…”
mentioning
confidence: 90%
“…Here, we present the first description of a brain abscess caused by Nocardia veterana. For 9 of the 13 patients, a clear underlying cause of an immunocompromised condition, such as the use of immunosuppressive drugs (4,14) or the presence of human immunodeficiency virus (HIV) infection (7,12) or of an autoimmune disorder such as systemic lupus erythematosus (SLE) (9,10,14), could be diagnosed. Four patients had no apparent cause of immunodeficiency (8,14,15).…”
mentioning
confidence: 99%
“…In a routine experiment using the highly conserved 16S rRNA gene primers pA (AGAGTTTGATCCTGGCTCAG) and pH (AAGGAGGTGATCCAGCCGCA) designed by Edwards et al (4) and used by others (6,12,13), we observed a number of unexpected PCR products with sizes ranging from 100 bp to more than 2.0 kb, in addition to the expected 1.5-kb band amplified from the 16S rRNA gene (Fig. 1, band D).…”
mentioning
confidence: 99%